Pretreatment HLADQA1-HLADRB1 Testing for the Prevention of Azathioprine-Induced Pancreatitis in Inflammatory Bowel Disease: A Prospective Cohort Study. Issue 4 (5th April 2021) - Wilson, Aze; Wang, Qian; Choi, Yun-Hee; Ponich, Terry; Gregor, James C.; Chande, Nilesh; Yan, Brian; Sey, Michael; Beaton, Melanie; Kim, Richard B.
Abstract : INTRODUCTION: Azathioprine-induced pancreatitis is an idiosyncratic and unpredictable response, occurring in up to 7% of azathioprine-exposed patients with inflammatory bowel disease (IBD). The haplotype HLADQA1-HLADRB1*07:01A>C is strongly associated with azathioprine-induced pancreatitis in IBD. We aimed to evaluate whether pretreatment HLADQA1-HLADRB1*07:01A>C screening will reduce the risk of azathioprine-induced pancreatitis. METHODS: Participants with IBD were screened for HLADQA1-HLADRB1*07:01A>C, and participants with a variant genotype were excluded from azathioprine treatment. Wild-type participants were started on azathioprine and followed for 3 months. The incidence of pancreatitis was compared with unscreened historical controls. RESULTS: HLADQA1-HLADRB1*07:01A>C screening resulted in an 11-fold reduction in the incidence of azathioprine-induced pancreatitis (n = 1/328 or 0.30% vs n = 13/373 or 3.4%). In propensity score-matched cohorts (age and sex), HLA DQA1-HLADRB1*07:01A>C screening was significantly associated with a reduction in the incidence of AZA-induced pancreatitis independent of weight, glucocorticoid exposure, and smoking status (adjusted odds ratio = 0.075, 95% confidence interval = 0.01–0.58, P = 0.01). Up to 45% (n = 271/599) of participants were excluded from azathioprine therapy based on the haplotype in the HLADQA1-HLADRB1*07:01A>C -screened cohort. DISCUSSION: HLADQA1-HLADRB1*07:01A>C screening reduced the risk of azathioprine-induced pancreatitis; however, using this strategy to guide the use of azathioprine therapy in IBD may eliminate a large proportion of patients from being eligible for treatment with azathioprine. In regions where there is access to other IBD therapies, and given the short-term and long-term toxicities associated with azathioprine, HLADQA1-HLADRB1*07:01A>C -screening may be a clinically relevant strategy for enhancing the safe use of azathioprine in IBD. In addition, cost-effectiveness analyses are needed to further solidify the utility of HLADQA1-HLADRB1*07:01A>C screening in IBD populations.